First-year seminars through the lens of Vincent Tinto's theories of student departure. A systematic review - Samoila, Magda Elena; Vrabie, Tina (Frontiers in Education, 2023)
Introduction Vincent Tinto is a towering figure in the study of dropout in higher education whose theory regarding student departure is a widely accepted contribution that explains how students become involved in the academic community and how their level of engagement impacts their decision to persist or to drop out. The aim of this study is to advance understanding of how Vincent Tinto's theories influence the current practices and support services offered by higher education institutions to freshman students through first-year seminars (FYS). Methods A systematic review was conducted based on peer-reviewed articles published between 2020 and 2022, selected through a multi-stage process. With reference to Tinto's contribution, this systematic review aims at providing answers to the following research questions: What are the methodological approaches identified in the studies under analysis? What knowledge can be identified in recent studies related to the categories of students attending FYS? What knowledge about students' personal and psychological characteristics with relevance for FYS can be found in recent studies? What knowledge about academic pedagogical and counseling factors with relevance for FYS can be found in recent studies? What knowledge about social and relational factors integration with relevance for FYS can be found in recent studies? Results The findings indicate three categories of studies that capitalize on Tinto's theories with regard to the design, conduct and evaluation of first-year seminars: a. studies that assess the role of students' personal and psychological variables, considered within FYS; b. studies that analyze the pedagogical and counseling interventions destined to students within FYS; c. studies that analyze the role of the social and relational dimension within FYS. Discussion The literature on the topic capitalizes on Vincent Tinto's contributions in relation to a student corpus which is extremely diverse in terms of age, socio-economic status, racial and cultural characteristics, attended specialization (a significant number of studies are destined to students who attend STEM specializations), generational characteristics (the example of first-generation students). Therefore, the interventions aimed at facilitating the integration of first-year students are carefully tailored and customized according to the needs of these categories of beneficiaries.